The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1002/asi.4630360610
|View full text |Cite
|
Sign up to set email alerts
|

The use of statistical methods in library and information science

Abstract: This study compared the use of statistics in 99 journals from four subject areas: library and information science, education, social work, and business. It was found that journals in library and information science produced more articles making no use of statistics than did journals in the other three subject areas, and that only in library and information science were there more articles using descriptive techniques only than articles using inferential techniques. A comparison of the mean number of articles p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Finally, in most of the literature of literature growth, the growth rates have been estimated by eye from the empirical plots and there is little use of more systematic methods such as fitting the data by least-squares (Tague et al, 1981). Such an observation corroborates those of Wyllys (1978) and Wallace (1985) who, in their studies of the use of statistics in the literature of L & IS, found that inferential statistics accounted for 2.9% and 6% of their samples, respectively. Descriptive statistics were used in 20% leaving a large 74% of the literature with no statistics at all (Wallace, 1985).…”
supporting
confidence: 90%
“…Finally, in most of the literature of literature growth, the growth rates have been estimated by eye from the empirical plots and there is little use of more systematic methods such as fitting the data by least-squares (Tague et al, 1981). Such an observation corroborates those of Wyllys (1978) and Wallace (1985) who, in their studies of the use of statistics in the literature of L & IS, found that inferential statistics accounted for 2.9% and 6% of their samples, respectively. Descriptive statistics were used in 20% leaving a large 74% of the literature with no statistics at all (Wallace, 1985).…”
supporting
confidence: 90%
“…Van De Water, Surprenant, Genova, & Atherton (1976Atherton ( ) 1969Atherton ( -1971Atherton ( and 1974 13.4% Wyllys (1978) 1975 3% Wallace (1985) 1981 6%…”
Section: Studiesmentioning
confidence: 99%
“…Notable scholars of librarianship including Butler (1933), Shera (1964), Goldhor (1972) and Busha and Harter (1980) lamented the lack of quantitative research in the field. Studies such as Wallace (1985) and Enger, Quirk, and Stewart (1988) used the presence of statistical methods to classify published articles in library journals as research. Other characteristics of division used to distinguish research publications have included the use of references in a given article.…”
Section: Criticisms Of How We Done It Goodmentioning
confidence: 99%